Long-term outcome of primary acute angle-closure glaucoma. Issue 4 (April 1985) - David, R.; Tessler, Z.; Yassur, Y.
Abstract : Factors influencing the long-term cure of 116 consecutive cases of acute angle-closure glaucoma, with at least one year's follow-up were examined. Delay in presentation and the time needed to terminate the attack were found to have a detrimental effect on the final outcome, while the height of the intraocular pressure at the time of the attack was found to be unimportant in predicting the long-term prognosis of the disease.